Arahan Pengurangan Risiko Bencana Tanah Longsor di Kawasan Objek Wisata Buntu Sopai Desa Marante Kabupaten Toraja Utara - Aprilia Laxsmi Pareang; Agus Salim; Tri Budiharto (Fakultas Teknik Universitas Bosowa, 2023)
This study aims to identify the level of hazard and vulnerability of landslides in the Buntu Sopai Tourism Area, Marante Village, North Toraja Regency, and propose directions for reducing the risk of landslides based on the level of vulnerability and vulnerability in the Buntu Sopai Tourism Object Area, Marante Village, District North Toraja. This study using basic physical condition analysis techniques, tourist attractiveness, vegetation density, scoring, overlay, and qualitative descriptive. As for the results of this study, it can be seen that the level of hazard in the Buntu Sopai Tourism Object Area is divided into 3, namely low, medium, and high haza levels. Likewise, the level of vulnerability in the Buntu Sopai Tourism Object Area is divided into 3 namely low, medium, and high vulnerability. Directions for reducing the risk of landslides consists of structural and non-structural mitigation, vegetative and mechanical mitigation, and based on the guidelines of UU No. 24 of 2007 regarding disaster management.